Effects of Liver-Regulating Herb Compounds on Varicocele-Associated Testicular Dysfunction Through Restoring Hormones and Spermatocytes Apoptosis - Jin, Guorong; Liu, Jianrong; Ding, Caiyun; Ma, Yuehong; Yin, Haizhen; Dong, Lina; Zhang, Fang; Qin, Qin; Gao, Songdan (Urology Journal, 2023)
Purpose: Varicocele is considered one of the causes of male infertility. Though varicocelectomy is supposed to improve semen parameters in adult infertile men, some patients with varicocele were still infertile after varicocelectomy. Previous studies showed Traditional Chinese Medicine, Liver-regulating herb compounds (LRHC) could improve the semen quality and increase fertility rates of infertile patients with varicocele. This study aimed to throw light on the mechanism of LRHC on varicocele-associated infertility. Materials and methods: Rats with varicocele-induced were treated with LRHC at dosage of 1mL/100g by intragastric administration for 90 days. The effects of LRHC on hormones and spermatocytes apoptosis were examined using ELISA assay, Western blotting, and flow cytometry. Results: Rats induced with varicocele showed a higher level of follicle stimulating hormone (FSH) in serum, which was brought back to normal level by LRHC. After treatment with LRHC, both testicular tissue in vivo and Sertoli cell TM4 cells in vitro showed elevated expressions of FSHR. Cell viabilities of TM4 cells and spermatocyte GC-2 cells were improved by LRHC treatment under normoxia and hypoxia conditions. Moreover, LRHC protected GC-2 cells from apoptosis induced by hypoxia. The expression of Bax reduced, while that of Bcl-2 increased after treatment with LRHC. Conclusion: This study revealed that LRHC had protective effects on spermatogenic disturbance caused by varicocele through regulating hormones and reducing spermatogenic cell apoptosis under hpoxia conditions.